Answer: x = 73/11 = 6.636
Step-by-step explanation:
1.) x-7/11-(6)=0
2.) simplify 7/11
3.) 7
(x - — —) - 6 = 0
11
4.) x x • 11
x = — = ——
1 11
5.) x • 11 - (7) 11x - 7
——————— = —————
11 11
6.) (11x - 7)
————— - 6 = 0
11
7.) 6 6 • 11
6 = — = ———
1 11
8.) (11x-7) - (6 • 11) 11x - 73
——————————— = ------------
11 11 11
9.) 11x - 73
————---- = 0
11
10.) 11x-73
—————— • 11 = 0 • 11
11
11.) Solve : 11x-73 = 0
Add 73 to both sides of the equation :
11x = 73
Divide both sides of the equation by 11:
x = 73/11 = 6.636
THE END